Pengaruh Partisipasi Anggaran terhadap Senjangan Anggaran dengan Asimetri Informasi, Penekanan Anggaran dan Komitmen Organisasional sebagai Variabel Pemoderasi - Irfan, Muh.; Santoso, Budi; Effendi, Lukman (Journal of Accounting and Investment, 2016)
This study aimed to examine the effect of budget participation toward budgetary slack with three moderating variables, namely: information asymmetry, budget emphasis and organizational commitment. Inconsistencies in previous studies on the effect of budget participation toward budgetary slack was become motivation in this study. Data were collected using a questionnaire distributed to the Local Governmentâ€™s Unit/SKPD Structural Officials of consisting of Echelon II, III and IV at the Regional Government ofÂ  Dompu Regency. Respondents was selected by purposive sampling method in which officers involved in the budgeting process, of the 100 distributed questionnaires, all questionnaires were returned. The analysis method employs variant-based SEM using SmartPLS Version 2.0 M3. The research instrument has passed the test of validity and reliability. The results showed that budget participation has an influence on budgetary slack. This research may prove interaction with information asymmetry budget participation, budget emphasis has a significant negative effect, while the organizational commitment significantly influence budgetary slack. The implications of this study that the interaction of budget participation on information asymmetry and budget emphasis can reduce budgetary slack, otherwise committed organizations can improve budgetary slack.